Consultancy, power and management ideas - the case of McKinsey & Co. - Sturdy, Andrew (Henry Stewart Talks, 2015)
Management ideas and power, Consultancy and power in McKinsey & Company, Professional consultant and manager (McKinsey), The war for talent (McKinsey), Healthcare privatization (McKinsey)